Problematika Pembelajaran Alquran di Kalangan Masyarakat Melayu Sambas, Indonesia (Analisis Kontrastif Titik Batas Fonem Bahasa Arab dan Melayu Sambas) - Azmi Azmi; Bayu Suratman (Universitas Islam Negeri Ar-Raniry Banda Aceh, Aceh, Indonesia., 2020)
The purpose of this research is to analyze the contrast between Arabic and Sambas Malay both at school and home of the Koran teacher. The method used in this research is qualitative research. The approach taken is descriptive based on interviews and in-depth observations at the research location. The location of the study was conducted in Seburing Village, Semparuk District, Sambas Regency, West Kalimantan Province, Indonesia. The selection of Seburing Village as a research location is because Malay people in Sambas are still not fluent in Arabic pronunciation and are brought in by mother tongue or Malay language Sambas. The results of this study indicate that the difficulty in speaking Sambas Malay in reciting Arabic, there are both vowel and consonant language sounds that have similarities and make students in MIS Nurul Huda or at the house of the teacher of the Koran experience errors, especially pronunciation.